The construction of intrahepatic cholangiocarcinoma model in zebrafish. Issue 1 (December 2017) - Wang, Jing; Leng, Xiaoqian; Wang, Guiping; Wan, Xiaoyang; Cao, Hong
Abstract Intrahepatic cholangiocarcinoma (ICC) is a highly malignant tumor, difficult to diagnose even at an early stage. In this study, we successfully constructed annras 61K -induced ICC model in zebrafish. Transcriptome analysis and gene set enrichment analysis (GSEA) of liver samples of the ICC and WT (wild-type) zebrafish revealed that the genes differentially expressed between the two groups were mainly involved in focal adhesion, chemokine signaling and metabolic pathways. Analysis of DNA methylomes revealed that compared with WT samples, methylated genes in ICC samples were enriched in functions associated with cellular, single-organism and metabolic processes. In particular, our result discovered eleven potential biomarker genes of ICC which were conserved between zebrafish and humans. Moreover, three potential biomarker genes were hypomethylated in the tumorigenesis of ICC:ehf, epha4 anditgb6 . In summary, our study provides a comprehensive analysis of molecular mechanisms accompanying the progressivenras 61K -induced ICC. This work indicates that our transgenic zebrafish could be a valuable model, not only for studying liver cancer, but also for exploring new therapeutic targets.